(untitled) (Iranian Journal of Kidney Diseases, 2016)
Esophageal perforation is a rupture of the esophageal wall, caused by iatrogenesis in 56% of cases. Perforation of the esophagus remains a challenge, and its incidence has increased as the use of endoscopic procedures has become more frequent. We report a 54-year-old woman with esophageal perforation 8 days after kidney transplantation. She had received a gastrointestinal consultation prior to her transplantation. This report highlights the fact that perforation may occur after any organ transplantation, especially during the initial 2 weeks after transplantation, when mycophenolate mofetil and cyclosporine as well as and high doses of corticosteroid are administered. If there is a delay in passage and a swallowing difficulty, high doses of immunosuppressive drugs are likely to cause ulceration and perforation. Preventive strategies including intravenous steroids for the first 2 to 3 weeks and divided doses of pills should be considered for such patients.